2017
DOI: 10.1111/resp.13234
|View full text |Cite
|
Sign up to set email alerts
|

Co‐morbidity and mortality among patients with interstitial lung diseases: A population‐based study

Abstract: Survival was impaired for patients with ILD for all levels of the DCcs, although increasing burden of co-morbidity tended to close the mortality gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
1
13
1
Order By: Relevance
“…These results are comparable to what has been observed in cohorts of other registry- based studies and publications [6, 1518]. Previous studies have also shown that cardiovascular diseases are more frequent in patients with IPF [18] as well as other ILDs [19] compared to matched controls.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are comparable to what has been observed in cohorts of other registry- based studies and publications [6, 1518]. Previous studies have also shown that cardiovascular diseases are more frequent in patients with IPF [18] as well as other ILDs [19] compared to matched controls.…”
Section: Discussionsupporting
confidence: 89%
“…While analyses on survival on the Australian cohort showed no effect on outcome, the cohort in Germany, where almost 90% of patients had one or more comorbidity, showed that the number of comorbidities were associated with mortality. A recent Danish study [19] on comorbidities and mortality in patients with ILDs, showed a significant difference in the frequency of comorbidities and mortality compared to age and gender matched non- ILD controls.…”
Section: Discussionmentioning
confidence: 99%
“…With updated IPF guidelines, it also became evident that referral to tertiary ILD centers with access to multidisciplinary discussions improved the diagnostic confidence concurrent with a reduced diagnostic latency and mortality [6,32,33]. By use of this guideline recommended multidisciplinary discussion approach from 2011 and onwards, we expect that the ICD10-codes registered during the observation period 2011-2017 actually represent true IPF diagnoses [34]. Finally, though the number of IPF cases are comparable to IPF cohorts in previous register-based IPF studies [9,[12][13][14], the small patient number, however, may limit the statistical precision.…”
Section: Discussionmentioning
confidence: 96%
“…A new cluster analysis among adults with various chronic ILD has been conducted, and four distinct clinical phenotypes were identified, allowing a better prediction of clinical outcomes than the current ILD diagnostic criteria. Having been said that genetic and environments are considerable impacting ILD epidemiology and natural history, we must not forget the role of co‐morbidities due to their impact on worsening of patient’s survival as seen in recent works conducted in Denmark and Germany along with the role of histopathological findings on disease progression …”
Section: Interstitial Lung Diseasementioning
confidence: 99%